2016
DOI: 10.1021/acs.cgd.6b00640
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Competition between Polymorphic Phases: Highlights on the Effect of Ostwald Ripening

Abstract: This is the supporting information for the paper: "Modeling the competition between polymorphic phases: highlights on the effect of Ostwald Ripening". Appendix A is the derivation of equation ( 18). Appendix B explains the demonstration of equation ( 23) from equation ( 22).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Our nanospectroscopy showed that, although the crystallinity index and vibrational exciton delocalization were overall correlated as could be expected, crystallite domain size remained small until the crystallinity index was very high, and significant short-range disorder remained, even with a high degree of long-range order. The observed aggregate ripening, increase in crystallinity, and increasing crystalline domain size are likely associated with Ostwald stages of growth, in which an amorphous phase is favored at early times to be replaced by an increasing fraction of a crystalline phase at longer annealing times (43)(44)(45)(46)(47). As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Our nanospectroscopy showed that, although the crystallinity index and vibrational exciton delocalization were overall correlated as could be expected, crystallite domain size remained small until the crystallinity index was very high, and significant short-range disorder remained, even with a high degree of long-range order. The observed aggregate ripening, increase in crystallinity, and increasing crystalline domain size are likely associated with Ostwald stages of growth, in which an amorphous phase is favored at early times to be replaced by an increasing fraction of a crystalline phase at longer annealing times (43)(44)(45)(46)(47). As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, to explain the Ostwald rule of stages using the dissolution resulting from the Gibbs Thomson effect, we present in this section the result of simulations done at low temperature. The parameters of the model, as well as the boundary conditions, were given in a previous work 20 . It is worth noting that supersaturation depletion was taken into account.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Others were calculated using nucleation data 25 . The interfacial energy values for α and β deduced from a comparative study 20 and used in the simulations are: = 0.013 ( . −2 ) and = 0.014 ( .…”
Section: Modelmentioning
confidence: 99%
“…Unfortunately, our understanding of these stages remains insufficient [26]. Because of the molecular-scale involved, numerous specifics of nucleation remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%